Effects of multiple relaxation times in the annular flow of pulsatile electro-osmotic flow of a complex biological fluid: blood with low and high cholesterol - Herrera-Valencia, Edtson Emilio; Ramírez-Torres, Luis Antonio; Soriano-Correa, Catalina; Sánchez-Villavicencio, Mayra Luz; Bautista, Oscar; Hernández-Abad, Vicente Jesús; Calderas, Fausto (Frontiers in Soft Matter, 2024)
This study investigates the electro-osmotic flow of biological fluid (blood with varying cholesterol levels) in annular flow to simulate a first approximation to arterial occlusion. The fluid´s rheology is characterized by a Multimodal Convected Maxwell model equation. The charge density follows the Boltzmann distribution, governing the electrical field. Mathematically, this scenario can be modeled by the Poisson-Boltzmann partial differential equation. Assuming a small zeta potential (less than 25mV) using the Debye-Huckel approximation, and considering a pulsatile electrical field, analytical solutions are derived using the Fourier transform formalism. These solutions, expressed in terms of modified Bessel function, provide transfer functions for axial velocity and volumetric flow as functions of material parameters represented by characteristic dimensionless numbers. The study further analyses thermal, electric, inertial, viscoelastic, and various interactions within the plasma, hematocrit, hematocrit-cholesterol, and cholesterol-cholesterol, as well as weight concentration through numerical simulations. Finally, the flow and rheology predictions are validated using experimental data on human blood with varying cholesterol levels. The obtained transfer functions reveal that the electric-thermalviscoelastic effects and the multiple geometric relationships contribute to the dynamic response of interactions between the input electrical field and output volumetric flow and shear stress functions, leading to and evolution of resonance curves. It is noteworthy that electro-osmotic flow in blood with pathologies associated with low and high cholesterol have been scarcely reported in the rheology literature. Thus, this work represents a significant contribution to the field. Keywords: (i) Human blood, (ii) High and low cholesterol, (iii) Pulsating electro-osmotic flow, (iv) Analytical solution, (v) Arterial occlusion.